In-canopy sprinkler application for corn: what works and what doesn't - Lamm, Freddie, author (Colorado State University. Libraries, 1997)
In-canopy sprinkler application in fully developed corn after tasseling is affected by nozzle spacing, nozzle height, row orientation with respect to center pivot travel, and nozzle type. Incorrect combinations can lead to poor in-canopy uniformity. In general, as nozzle spacing increased from 5 to 10 ft, in-canopy uniformity decreased. The 4 ft nozzle height was worse than the 2 and 7 ft nozzle heights in terms of in-canopy uniformity. Circular (parallel to sprinkler travel) rows almost always have better in-canopy uniformity than straight (perpendicular to sprinkler travel) rows. Spinner nozzles had better in-canopy uniformity than plate nozzles at the 2 and 7 ft heights.
Not digitized by CSUL Digital Services.
Presented at the Central Plains irrigation short course and exposition on February 4, 1997 at the Colby Community Building in Colby, Kansas.